Presentation - Editors (Revista do Colóquio, 2022)
Under the title “Inhabitable Worlds: Images, Bodies, Places and Discourses”, the twentieth issue of the Colloquium Journal brought a diverse set of works that discuss creative and research processes in different contexts, including reports of practical experiences and theoretical elucidations. That set of works represented a small part of what we would have liked to have released for the edition. Unfortunately, time and the editing processes often do not allow us to publish all the quality works we receive in a single edition. In some cases, the research that is not published in that specific edition is in line with the theme proposed for the following editions and, in this context (and due to the patience of the authors), is published several months after its submission and evaluation. For a variety of reasons, ranging from the urgency of authors to publish their articles (a condition resulting from the productivity pressures of academia) to subtle editorial disagreements, many of these studies are not published on our pages. We always regret when we are unable to work on some texts in more time and, therefore, lose the opportunity to include them in our next issues.